Percepções maternas sobre visitas domiciliares na gestação e no primeiro ano de vida do bebê: um estudo com mães do programa primeira infância melhor - Schneider, Alessandra (Universidade do Vale do Rio do Sinos, 2010)
Home visiting has been used worldwide in early childhood development programs, aiming at the improvement of both health and development conditions, especially during pregnancy and the early years of the child’s life, and mainly for families living in vulnerable conditions. A number of studies have been developed for the purpose of assessing such programs, based on the evidence on results and effects of interventions that will be made known years later, mainly using quantitative methodology. Few studies use a qualitative approach and focus on perceptions on the programs, either by the visitors or the beneficiaries. The present study aims at analyzing maternal perceptions on home visiting under the Programa Primeira Infância Melhor (A Better Early Childhood Program) during pregnancy and the infant’s first year of life. This Program was introduced in Rio Grande do Sul in 2003, and inspired, years later, a State Law with the same goal. A qualitative exploratory transversal study was carried out, based on the Mult
Keywords: políticas públicas; relação mãe-bebê; visitas domiciliares; desenvolvimento infantil; home visiting; mother-infant relationship; public policies; child development; Ciências Humanas